Effects of closed-loop stimulation vs. DDD pacing on haemodynamic variations and occurrence of syncope induced by head-up tilt test in older patients with refractory cardioinhibitory vasovagal syncope: the Tilt test-Induced REsponse in Closed-loop Stimulation multicentre, prospective, single blind, randomized study. Issue 5 (12th April 2017) - Palmisano, Pietro; Dell'Era, Gabriele; Russo, Vincenzo; Zaccaria, Maria; Mangia, Rolando; Bortnik, Miriam; De Vecchi, Federica; Giubertoni, Ailia; Patti, Fabiana; Magnani, Andrea; Nigro, Gerardo; Rago, Anna; et al.
Abstract: Aims: Closed-loop stimulation (CLS) seemed promising in preventing the recurrence of vasovagal syncope (VVS) in patients with a cardioinhibitory response to head-up tilt test (HUTT) compared with conventional pacing. We hypothesized that the better results of this algorithm are due to its quick reaction in high-rate pacing delivered in the early phase of vasovagal reflex, which increase the cardiac output and the blood pressure preventing loss of consciousness. Methods and results: This prospective, randomized, single-blind, multicentre study was designed as an intra-patient comparison and enrolled 30 patients (age 62.2 ± 13.5 years, males 60.0%) with cardioinhibitory VVS, carrying a dual-chamber pacemaker incorporating CLS algorithm. Two HUTTs were performed one week apart: one during DDD-CLS 60–130/min pacing and the other during DDD 60/min pacing; patients were randomly and blindly assigned to two groups: in one the first HUTT was performed in DDD-CLS ( n  = 15), in the other in DDD ( n  = 15). Occurrence of syncope and haemodynamic variations induced by HUTT was recorded during the tests. Compared with DDD, DDD-CLS significantly reduced the occurrence of syncope induced by HUTT (30.0% vs. 76.7%; P  < 0.001). In the patients who had syncope in both DDD and DDD-CLS mode, DDD-CLS significantly delayed the onset of syncope during HUTT (from 20.8 ± 3.9 to 24.8 ± 0.9 min; P  = 0.032). The maximum fall in systolic blood pressure recorded during HUTT was significantly lower in DDD-CLS compared with DDD (43.2 ± 30.3 vs. 65.1 ± 25.8 mmHg; P  = 0.004). Conclusion: In patients with cardioinhibitory VVS, CLS reduces the occurrence of syncope induced by HUTT, compared with DDD pacing. When CLS is not able to abort the vasovagal reflex, it seems to delay the onset of syncope.